Small Medium Business in Surabaya and Surrounding Neighbour City on using Internet Technology while facing MEA - Rinabi Tanamal; Tony Antonio (Jurnal Eksplorasi Karya Sistem Informasi dan Sains, 2016)
Facing MEA or AEC, small medium business in these ASEAN countries member are now facing competition among itself. The Organisations need to adopt new technologies where resources are limited, limited on knowledge, so organisation need to be innovative and creative or they will perish if nothing to be improved. This study emphasize on the importance of SME (Small Medium Enterprise) in Surabaya city region and the analyses combining the TAM Model, TOE Framework as well  as  two sample test on 246 respondent especially on using The Internet Technology. The conclusions created further study on environment context and other technology adoption by SME